Improvement of the method of the multiclass Pap smear image segmentation based on cross-domain transfer learning with limited data - Nurtay, Margulan; Alina, Gaukhar; Tau, Ardak (Eastern-European Journal of Enterprise Technologies, 2026)
This study examined automated multi-class semantic segmentation of Pap smear images used for cervical cancer detection. The effectiveness of existing deep learning methods is often limited due to a lack of labeled data, high morphological variability of cervical cells, overlapping structures, noise, low contrast, and imaging artifacts characteristic of cytology specimens. In this study, the authors propose a cross-domain transfer learning approach that adapts pre-trained deep neural networks to the task of multi-class Pap smear segmentation. All networks were pre-trained on large-scale natural image datasets. In the experiments, both convolutional neural networks and Transformer-based models, including hybrid configurations, were refined and systematically compared. Network performance was assessed using quantitative metrics (Dice score, IoU, HD95), as well as qualitative visual assessment of segmentation edges and boundaries. The results obtained from the experiments showed that Transformer-based architectures, in particular SegFormer, significantly outperform convolutional models when processing noisy and heterogeneous cytological data. Using specialized data augmentation strategies developed specifically for medical imaging, SegFormer increased Dice scores to 0.95 across all classes (healthy, unhealthy, rubbish, both cells), as well as improved edge accuracy and robustness to artifacts and cell aliasing. Multi-scale feature extraction and global context modeling proved essential for accurately identifying cellular structures in data-constrained settings. The results obtained in the study can help in the development of reliable automated diagnostic tools to assist cytopathologists, as well as to improve the overall accuracy and efficiency of cervical cancer screening programs